2011
DOI: 10.1039/c0cp02657c
|View full text |Cite
|
Sign up to set email alerts
|

Amontonian frictional behaviour of nanostructured surfaces

Abstract: With nanotextured surfaces and interfaces increasingly being encountered in technological and biomedical applications, there is a need for a better understanding of frictional properties involving such surfaces. Here we report friction measurements of several nanostructured surfaces using an Atomic Force Microscope (AFM). These nanostructured surfaces provide well defined model systems on which we have tested the applicability of Amontons' laws of friction. Our results show that Amontonian behaviour is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
(49 reference statements)
10
38
0
Order By: Relevance
“…In addition, the longer pillars exhibited a higher friction coe cient than the shorter ones, as the longer pillars underwent more elastic deformation which led to an increase in the contact area. Thormann The oscillations in the shear traces observed by Pilkington et al 19 are similar to the stick-slip behaviour between two sliding surfaces under certain conditions. Stick-slip motion can be found at all length scales, ranging from the atomic scale up to the macroscale where stick-slip is responsible for common-life phenomena such as the noise of squeaking doors and car brakes' squeal.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…In addition, the longer pillars exhibited a higher friction coe cient than the shorter ones, as the longer pillars underwent more elastic deformation which led to an increase in the contact area. Thormann The oscillations in the shear traces observed by Pilkington et al 19 are similar to the stick-slip behaviour between two sliding surfaces under certain conditions. Stick-slip motion can be found at all length scales, ranging from the atomic scale up to the macroscale where stick-slip is responsible for common-life phenomena such as the noise of squeaking doors and car brakes' squeal.…”
supporting
confidence: 67%
“…A nite friction force f 0 extrapolated at zero load can be attributed to the contributions by the adhesive force which can be considered as an e ective load, as shown in the equation derived by Derjaguin: The apparent linear relationship between f s and L exhibited here is consistent with previous frictional studies on nanostructured surfaces. For instance, such a behaviour has previously been reported by Pilkington et al 19 on surfaces bearing nanoseeds, nanodiamonds, nanodomes and nanorods and in that study the linear relationship was discussed using various existing models. At the microscale, the linear nature of the friction-load relationship is commonly explained using models based on the Bowden and Tabor theory, 46 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 However, such a linear relationship between f s and L has not always been observed for surfaces with nanotextures.…”
Section: Friction-load Relationshipmentioning
confidence: 66%
See 2 more Smart Citations
“…The result revealed that the friction force varied linearly with the normal load, but the magnitude of the friction force was high relative to that on a smooth nickel surface. Pilkington et al [20] reported that the friction behavior of nanopatterned surfaces, including ZnO nanorods, ZnO nanograins, Al 2 O 3 nanodomes and nanodiamonds, obeys Amontons' law. Conversely, other authors reported that Amontons' law is no longer valid for a nanopatterned surface.…”
Section: Introductionmentioning
confidence: 99%